2018
DOI: 10.1002/oby.22317
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training and Protein Supplementation Increase Strength After Bariatric Surgery: A Randomized Controlled Trial

Abstract: Objective Physical activity and dietary regimens to optimize health outcomes after bariatric surgery are not well known. This study aimed to determine whether resistance training with dietary protein supplementation is effective in maintaining body composition and physical fitness after obesity surgery. Methods Seventy‐six women with obesity undergoing Roux‐en‐Y gastric bypass were randomly assigned at the time of surgery to receive either usual care (controls [CON], n = 22), usual care and additional (whey) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
160
1
23

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(188 citation statements)
references
References 46 publications
4
160
1
23
Order By: Relevance
“…Interestingly, in a retrospective study of 100 patients after RYGB or sleeve gastrectomy, Smelt and colleagues found that post-operative handgrip strength, reflecting muscle strength, was impacted significantly by protein intake [51]. Oppert and colleagues went further with an 18-week, randomized, controlled trial assigning 26 obese women operated by RYGB to a control group, a group supplemented with whey protein, two powder drinks per day at a dose of 48 g/day, and a group combining resistance training 3 times per week with whey supplementation [52]. While they did not uncover a significant difference in lean mass loss between groups, for patients completing the whole study the muscle strength in lower and upper limbs relative to body weight and the protein intakes improved significantly in the group combining exercise and protein supplementation.…”
Section: Bariatric Surgery and Protein Changesmentioning
confidence: 99%
“…Interestingly, in a retrospective study of 100 patients after RYGB or sleeve gastrectomy, Smelt and colleagues found that post-operative handgrip strength, reflecting muscle strength, was impacted significantly by protein intake [51]. Oppert and colleagues went further with an 18-week, randomized, controlled trial assigning 26 obese women operated by RYGB to a control group, a group supplemented with whey protein, two powder drinks per day at a dose of 48 g/day, and a group combining resistance training 3 times per week with whey supplementation [52]. While they did not uncover a significant difference in lean mass loss between groups, for patients completing the whole study the muscle strength in lower and upper limbs relative to body weight and the protein intakes improved significantly in the group combining exercise and protein supplementation.…”
Section: Bariatric Surgery and Protein Changesmentioning
confidence: 99%
“…However, at the end of the study period, both groups displayed similar food pattern. Likewise, another recent RCT comparing protein supplementation with or without resistance training to usual follow-up in an unselected bariatric cohort did not evidence any difference in weight or body composition outcomes [67]. Overall, these data could suggest that synergic interventions post-BS should be proposed in selected individuals predicted to display a poor response (either poor weight-loss [61] or non-diabetes remission or diabetes relapse [64]) or at risk to display adverse surgery outcomes (bone fractures) to evaluate whether it improves further health outcomes.…”
Section: Functional Food Health Outcomes and Bariatric Surgery: Persmentioning
confidence: 93%
“…Participants in the CON group were recruited among bariatric surgery patients with non‐syndromic obesity and had been included in a previous clinical trial (ClinicalTrials.gov website: NCT01113996). Data were collected from this group pre‐surgery, and details of this study, which was entirely performed at our university medical centre, can be found elsewhere (Oppert et al, ). Each participant of the PWS group was individually matched with two control participants for gender, age and per cent body fat.…”
Section: Methodsmentioning
confidence: 99%
“…PA and sedentary time were measured using a tri‐axial GT3x Actigraph accelerometer (Manufacturing Technology, Inc.), as previously described (Oppert et al, ). Participants were asked to wear the accelerometers at the hip using an elastic belt for seven consecutive days during all waking hours except during water‐based activities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation